Salt Tolerance studies: Effect of Soil Salinity on the Growth and Chemical Composition of Plants- Part II - Mehta, B V; Desai, R S (Journal of Soil and Water Conservation, 2022)
The normal mineral cotnposition of a plant is frequently altered under saline conditions. Factors that inhibit plant growth such as mineral deficiencies or excess and high moisture tension may result in abnormal accumulation of ions in plant tissues. For example, plants deficient in potassium may often show greater accumu- lation of calcium magnesium or sodium than normal plants10. Owing to high degree of variability in the composition of normal plants under diverse growing conditions, the chemical composition of plant parts should be considered as one line of evidence in the diagnosis of crop injury on saline soils. It has been shown in Part I of this series that in the salt treatments applied for different crops like bajri ( Pennisetunz typhoidewn, Rich.), tobacco ( Nicotiana tabacwn, L.) , cotton ( Gossypiunt herbaeunt, L.), beans ( Dolichos lablab, L.) , tomato ( Lycopersicwn esculentunz, Mill ) , guvar ( Syaønoøsis psora- lioides ), cabbage ( Brassica oleraca, L.) and peas ( Pisum sativum ) up to certain concen- trations of applied salt the plant growth is unaffected and above these, there is visible salt injury, while at still higher concentrations the plant is unable to survive. At these important levels, the chemical com- position of the plant is expected to give important information regarding the profound changes taking place in them. To get in- formation on these points, the leaves of plants grown under different levels of applied salt were analysed for calcium, magnesium, potassium, sodium, chlorine and nitrogen contents. In the case of tobacco, nicotine and total sugars were also determined, as these constituents affect the quality of tobacco leaf.